Longitudinal and shear ultrasonic measurements in vegetable oils - PŁOWIEC, R.; BALCERZAK, A. (Archives of Acoustics, 2000)
In this paper the results of ultrasonic longitudinal and shear measurements in vegetable oils are presented and discussed. The run of the ultrasonic attenuation suggests a relaxation process at frequencies below 0.5 MHz. Another one is suggested at low temperature in the vicinity of 1 Hz.